Measuring the malaysian islamic subsidiaries and commercial banks’ efficiency - Ahmad, Suraya; Wan Jusoh, Wan Noor Hazlina; Abdul Rahman, Abdul Rahim (2012)

(untitled)
This study measures and ranks the relative efficiency of the domestic Islamic subsidiaries and commercial banks in Malaysia from the year 2008 to 2010. Nine domestic commercial banks and nine Islamic subsidiaries are selected. The study uses the Data Envelopment Analysis as the method to measure the relative efficiency of the selected banks in intermediating personnel expense and total customer deposits (i.e. inputs) into total loan (i.e. output). The study focuses on the technical efficiency, pure technical efficiency and scale efficiency. This study found that the technical inefficiency of the selected banks in 2008 was due to the pure technical inefficiency. This indicated that the scale efficiency was higher than the pure technical efficiency. However, in 2009 and 2010, the pure technical efficiency was higher compared to the scale efficiency. Hence, the technical inefficiency was due to the scale inefficiency